New Methods for Delivering Human ServicesJonesG. Brian, DaytonCharles, and GelattH. B. New Methods for Delivering Human Services (New York: Human Sciences Press, 1977), 140 pp., $10.95. - Schermerhom, John R. (Academy of Management Review, 1979)
This article presents a review of the book “New Methods for Delivering Human Services,” by G. Brian Jones, Charles Dayton and H. B. Gelatt.